Biomineralized iron oxide–polydopamine hybrid nanodots for contrast-enhanced T1-weighted magnetic resonance imaging and photothermal tumor ablation. Issue 7 (17th February 2021) - Wang, Ze'ai; Wang, Yanfeng; Wang, Yuan; Wei, Chaogang; Deng, Yibin; Chen, Huabing; Shen, Junkang; Ke, Hengte
Abstract : Biomineralized iron oxide–polydopamine hybrid nanodots are constructed using albumin nanoreactors to facilitate contrast-enhanced T 1 -weighted magnetic resonance imaging as well as photothermal therapeutic efficacy. Abstract : Iron oxide nanoparticles (IO NPs) have become the focus of molecular imaging probes for contrast enhanced magnetic resonance (MR) imaging due to their intrinsic magnetic and biodegradable properties, as well as long blood half-lives and low toxicity. Massive efforts have been made to explore the IO NPs as T 2 -weighted MR contrast agents, which have high susceptibility to induce a long-range magnetic field that interferes with diagnosis. Thus, the development of IO NPs with potent T 1 relaxivity might help in providing an alternative for clinically applied gadolinium chelates. Herein, biomineralized iron oxide–polydopamine hybrid nanodots (IO/PDA-NDs) have been constructed using albumin as the nanoreactors to induce nanoprecipitation and polymerization simultaneously, facilitating T 1 -weighted contrast-enhancement as well as photothermal therapeutic capability. The IO nanoclusters in IO/PDA-NDs have an r 1 relaxivity of 5.79 mM −1 s −1 with a relatively low r 2 / r 1 ratio of 1.71, demonstrating the preferable iron oxide based T 1 contrast agents. The high photothermal conversion coefficient and tumor targeting effect of the hybrid nanodots could result in complete tumor ablation efficacy. The biomineralization method provides a promising approach for the integration of tumor diagnosis and treatment to achieve efficient cancer theranostics.